Medication use among children 0-14 years old: population baseline study - Maria J.B. Cruz; Lays F.N. Dourado; Emerson C. Bodevan; Renata A. Andrade; Delba F. Santos (Elsevier, 2014)
OBJECTIVE: Determine the prevalence of medication use in children and adolescents in 20 municipalities of Vale do Jequitinhonha, Minas Gerais-Brazil, showing the main groups and variables that may have influenced use. METHODS: Descriptive population-based survey sample of 555 interviews, selected by simple random cluster sampling of 137 census tracts. Inclusion criteria were age ≤ 14 years, mandatory interview with the legal guardians, and regardless of having received medications. Regarding the usage pattern, participants were divided into two groups: consumption and non-consumption of drugs. A descriptive analysis of the variables and tests of association were performed. RESULTS: The prevalence of drug consumption was 56.57%, and 42.43% showed no consumption. The use of medicinal plants was 72.9% for drug users and 74.3% for non-users. The health conditions for consumption were cough, common cold, flu, nasal congestion or bronchospasm (49.7%), fever (5.4%), headache (5.4%), diarrhea, indigestion, and abdominal colic (6.7%). In cases of self-medication, 30.57% of the drugs were given by the mother, and 69.42% were prescription drugs. Self-medication was prevalent using paracetamol (30.2%), dipyrone (20.8%), and cold medicine (18.8%). There was increased use of analgesics/antipyretics, followed by respiratory medications, systemic antibiotics, histamine H1 antagonists, and vitamins/antianemics. CONCLUSIONS: The prevalence of drugs use in children was high, indicating the need for formulating educational programs aiming at the awareness of caregivers regarding rational use.